(untitled) (Khairulummah, 2025)
This research paper provides a comprehensive analysis of the role of opposition parties in shaping the democratization process in Pakistan between 2013 and 2022. Relying primarily on interviews and other qualitative data investigates into how opposition parties responded to key political events and challenges that defined this period. One of the central issues examined is the controversial general elections of 2013 and 2018, both of which were accompanied by widespread allegations of rigging and manipulation. These elections not only sparked intense reactions from opposition parties but also triggered significant political instability across the country. The research paper also explores the aftermath of these elections, particularly focusing on how political instability deepened after 2013. This instability created an instable environment where opposition parties played a crucial role in questioning the legitimacy of the ruling governments and calling for reforms in the electoral process. Paper addresses the intervention of apolitical actors, which further complicated the democratic process. Such interventions often led to compromised parliamentary supremacy, with non-political actors influencing key decisions and undermining democratic institutions. Another important theme is the increasing use of un-parliamentary and inflammatory rhetoric during this period. The political discourse between opposition parties and the government became increasingly hostile, contributing to a growing divide within the politics. It also examines issues related to accountability and political victimization, where opposition parties frequently accused the ruling government of targeting political opponents under the guise of accountability measures. Finally, the dissension between the government and opposition parties is discussed in detail, highlighting how this conflict hindered constructive dialogue and progress towards a more stable democratic system. This analysis aims to provide a deeper understanding of the challenges faced by Pakistan’s democratic institutions during these critical years.